A practical guide to the 2003 ISDA credit derivatives definition - Harding, Paul C., 1951- (London: Euromony Books, 2004)
A user-friendly guide to the complex Definitions for market practitioners and those new to credit derivatives documentation. In addition to a comprehensive definitions section, this book ensures that you understand the evolution of the global credit derivatives market, the main credit derivative products and risks associated with them. It also covers the legal issues affecting credit derivatives, some causes celebres and new developments in the credit derivatives market (including master confirmation agreements, credit risk, bilateral contracts, restructuring, securitization, ISDA credit derivatives documentation projects and electronic processing of credit derivatives contracts). The book also includes a glossary of key terms used in the Definitions and reproduction of the Definitions, the May 2003 Supplement to the Definitions and the 60 Business Day cap side letter all reproduced with the kind permission of the International Swaps and Derivatives Association, Inc.
Includes index.
rpm 10/09/13
Loans
Keywords: Credit derivatives; Credit.